Plant regeneration from embryogenic and organogenic calli in oat - Bered, Fernanda; Cruz de Melo Sereno, Maria Jane; Félix de Carvalho, Fernando Irajá; Erna Lange, Claúdia; Luise Handel, Cristine; Cunha Dornelles, Ana Lúcia (Pesquisa Agropecuaria Brasileira, 1998)
Nine oat (Avena sativa L.) genotypes were evaluated aiming to test in vitro regeneration ability. Immature embryos between 1 and 3 mm were inoculated in MS medium supplemented with 4 mg/L of 2,4-D. In the next stage, 2,4-D was reduced, and then removed at the plant regeneration stage. The obtained calli were tested for somatic embryoids production. The correlation between this character and the regeneration was tested. Plant regeneration was observed for all genotypes; however, variability was detected for this character. The embryogenesis x regeneration analysis revealed low correlation between these characters, showing that plant regeneration may have occurred preferentially via organogenesis and germination.